Perbandingan Penerapan Standar Akuntansi Keuangan Terhadap Asuransi Syariah dan Asuransi Konvensional Pada Contract Insurance: Studi Literatur - Dwi U. Wardoyo; Gita B. Febrianti; Sri Rahmayani; Aldini F. Fahrezi; Bintang J. Airlangga (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The development of insurance companies in Indonesia resulted in two types of insurance companies, in line with the growth of conventional insurance companies with this triggered the establishment of Islamic insurance companies.Thus, the study aims to compare the application of the standard financial accounting on sharia insurance and conventional insurance on insurance contracts. Our review consists of 20 literary references to the application of the standard financial accounting on man-insurance and conventional insurance published from 2011 to 2021. Results have shown that a PSAK application is different between sharia and conventional insurance. The PSAK on which sharia insurance is used is PSAK 108 and PSAK 101, while conventional insurance uses three PSAK made up of PSAK 28, PSAK 36, and PSAK 62. Accordingly, we hope that the resulting review will contribute to a literature study on the application of the standard financial accounting on sharia insurance and conventional insurance on the insurance contract.